1989
DOI: 10.1073/pnas.86.2.690
|View full text |Cite
|
Sign up to set email alerts
|

De novo amplification within a "silent" human cholinesterase gene in a family subjected to prolonged exposure to organophosphorous insecticides.

Abstract: A 100-fold DNA amplification in the CHE gene, coding for serum butyryicholinesterase (BtChoEase), was found in a farmer expressing the "silent" CHE phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
28
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…cently cloned human ACHEcDNA (1) and CHEcDNA (2), we found that the CHE gene is capable of being heritably amplified in humans (8). Further analysis revealed the occurrence of coamplified ACHEDNA and CHEDNA sequences in genomic DNA from peripheral blood cells of leukemic patients (9).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…cently cloned human ACHEcDNA (1) and CHEcDNA (2), we found that the CHE gene is capable of being heritably amplified in humans (8). Further analysis revealed the occurrence of coamplified ACHEDNA and CHEDNA sequences in genomic DNA from peripheral blood cells of leukemic patients (9).…”
Section: Introductionmentioning
confidence: 90%
“…32P and 35S-labeled cDNA and plasmid probes were labeled by the multi-prime labeling method (Boehringer Mannheim Biochemicals, Indianapolis, IN) to specific activities of 1-5 X 10 9 dpm/gg DNA using enzymatically restricted and gel electroeluted DNA fragments (2,8). DNA (9) and RNA (2) blot hybridizations were performed as previously described, and washes were at 65°C at low ionic strength (0.…”
Section: Methodsmentioning
confidence: 99%
“…Yet another possibility is that of the insertion of a retroviral sequence, followed by the extension of its amplification into the chromosomal region of the ChoEase genes. The amplification of the CHE gene on chromosome 3 that we recently found in a family exposed to chronic doses of parathion, a potent ChoEase inhibitor (19), could be an example for the first option. It should be noted, however, that in that particular family the CHE gene was the only one to be amplified (H.S., C.A.P., and H.Z., unpublished observation).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the amplification of oncogenes occurs at a very high frequency in human malignancies and is usually correlated with the more progressive stages of the particular disease {Bishop 1987; Hamlin et al 1991). With very rare exceptions (see Prody et al 1989), DNA sequence amplification has not been observed in normal, non-neoplastic cells (Sager et al 1985;Otto et al 1989;Tlsty 1990;Wright et al 1990). …”
mentioning
confidence: 99%